The Effect of Preventive Agents (Mouthwashes/Gels) on the Color Stability of Dental Resin-Based Composite Materials - Khalid H. Al-Samadani (MDPI AG, 2017)
The color of dental restorative material should be maintained throughout its functional lifetime in an oral environment. However, the frequent use of mouthwash may affect the color stability of these composite restorations. The aim of this study is to assess the effects of using various mouthwashes on the color stability of various dental restorative composite materials. For this purpose, four mouthwashes/gels (Flocare gel (0.4% stannous fluoride), Pascal gel (topical APF fluoride), Pro-Relief mouthwash (sodium fluoride), and Plax Soin mouthwash (sodium fluoride)), and distilled water as a control, were selected. These were divided into five groups: Group 1: Flocare gel; Group 2: Pascal gel; Group 3: Pro-Relief mouthwash; Group 4: Plax Soin mouthwash; and Group 5: distilled water (control). Prepared restorative materials samples were immersed in the groups of mouthwashes/gels and the distilled water (control) for 24, 48, and 72 h. The discoloration that all materials exhibited with all immersion groups was significantly different at each of the three time periods for all groups (p < 0.05). Results from immersion in Flocare gel, Pascal gel, Pro-Relief mouthwash, and Plax Soin mouthwash were statistically significant (p < 0.05). The color change chroma was not significant for Pro-Relief and Plax Soin mouthwash (p > 0.05). Mouthwashes/gels affect color shifting for all composite resin materials, and changes are exaggerated over time. However, discoloration effects are not perceptible to the human eye.